2017
DOI: 10.1137/15m1043972
|View full text |Cite
|
Sign up to set email alerts
|

On the Absence of Uniform Recovery in Many Real-World Applications of Compressed Sensing and the Restricted Isometry Property and Nullspace Property in Levels

Abstract: The purpose of this paper is twofold. The first is to point out that the Restricted Isometry Property (RIP) does not hold in many applications where compressed sensing is successfully used. This includes fields like Magnetic Resonance Imaging (MRI), Computerized Tomography, Electron Microscopy, Radio Interferometry and Fluorescence Microscopy. We demonstrate that for natural compressed sensing matrices involving a level based reconstruction basis (e.g. wavelets), the number of measurements required to recover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…There have also been several theoretical extensions. First, generalizations of the RIP for the setting of asymptotic sparsity, asymptotic incoherence and multilevel random subsampling have been introduced and analysed in [9,60,80]. These complement the results proved in this paper by establishing uniform recovery guarantees.…”
Section: Relation To Other Worksupporting
confidence: 52%
“…There have also been several theoretical extensions. First, generalizations of the RIP for the setting of asymptotic sparsity, asymptotic incoherence and multilevel random subsampling have been introduced and analysed in [9,60,80]. These complement the results proved in this paper by establishing uniform recovery guarantees.…”
Section: Relation To Other Worksupporting
confidence: 52%
“…We prove a robustness under unknown error for the WSR-LASSO decoder (11). Our theory suggests that the tuning parameter should be chosen directly proportional to the quantity K(s).…”
Section: Robustness Of Wsr-lassomentioning
confidence: 81%
“…Then, the following holds with probability at least 1 − ε. For any f ∈ L 2 ν (D) ∩ L ∞ (D) expanded as in (3), the approximationf defined as in (13) computed using the WSR-LASSO decoder (11) with tuning parameter…”
Section: Robustness Of Wsr-lassomentioning
confidence: 99%
“…Now that we have a good concept of sparsity in a level based reconstruction basis, it is time to define an analogue to the RIP. The natural adaptation, which we term the 'RIP in levels' (as described in [12]), is defined as follows:…”
Section: Mathematically Modelling Cs a (Sm)-sparsity And The Rmentioning
confidence: 99%
“…It is worth noting that although Theorem 2 reduces to a standard result on the RIP in the case that l = 1, the requirement on δ s,M involves the number of levels l and a parameter η s,M . Further work in [12] has shown that this requirement cannot be avoided.…”
Section: Deterministic Sampling In Compressed Sensingmentioning
confidence: 99%